2004
DOI: 10.1016/j.yexcr.2004.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of cellular contractility to spatial and temporal variations in cellular stiffness

Abstract: Scanning probe microscopy and immunofluorescence observations indicated that cellular stiffness was attributed to a contractile network structure consisting of stress fibers. We measured temporal variations in cellular stiffness when cellular contractility was regulated by dosing with lysophosphatidic acid or Y-27632. This experiment reveals a clear relation between cellular stiffness and contractility: Increases in contractility cause cells to stiffen. On the other hand, decreases in contractility reduce cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 42 publications
5
31
1
Order By: Relevance
“…Experiments concerned changes in cell stiffness upon increasing Ca 2+ concentration [939,940] or the cellular contractility [941]. Also, the effect of cell differentiation [942], cell division [943], shear stress [917,944], culture time [307], and cell spreading [945] has been studied.…”
Section: Filled Polyelectrolyte Capsulesmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments concerned changes in cell stiffness upon increasing Ca 2+ concentration [939,940] or the cellular contractility [941]. Also, the effect of cell differentiation [942], cell division [943], shear stress [917,944], culture time [307], and cell spreading [945] has been studied.…”
Section: Filled Polyelectrolyte Capsulesmentioning
confidence: 99%
“…Results for the lactic acid bacteria could be explained on the basis of the different constituents of the cell surfaces (S-layer proteins, polysaccharides, lipoteichoic acids) present in the different strains. For more detailed understanding of the mechanical properties of cells, force volume imaging has been combined with chemical modification of different components of the cytoskeleton, like actin [941,1208,1211,1212], vinculin [1161,1213], actomyosin [1214], and microtubules [941,1215].…”
Section: Force Volume Modementioning
confidence: 99%
“…To measure the contractile force in a single cell, we used a mechanical-scanning probe microscope (M-SPM), which can visualize the spatial distribution of stiffness reflected by the tension in the stress fibers in a cell (Nagayama et al, 2004). By using the M-SPM, we were 4 successful in observing a dramatic change in cellular stiffness during cell migration (Nagayama et al, 2001) and in discovering tensional homeostasis against external deformation (Mizutani et al, 2004a).…”
Section: Introductionmentioning
confidence: 99%
“…By using the M-SPM, we were 4 successful in observing a dramatic change in cellular stiffness during cell migration (Nagayama et al, 2001) and in discovering tensional homeostasis against external deformation (Mizutani et al, 2004a). Our previous work showed that cellular stiffness increased on stimulation with lysophosphatidic acid (LPA) (Nagayama et al, 2004) that is a RhoA activator. Taking these findings into consideration, we concluded that the phosphorylation of MRLC increases cellular stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…We modified the M-SPM to enable visualization of topography and local stiffness in living cells in order to investigate the cellular stiffness and mechanical response of the cells toward external loading force using force mapping mode under liquid conditions [10,11]. In order to measure the mechanical properties of a tissue-like material under an external loading force, we developed wide-range scanning probe microscopy (WR-SPM), which is a modification of a commercial M-SPM [12].…”
Section: Introductionmentioning
confidence: 99%